2013
DOI: 10.14205/2310-6980.2013.01.02.1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Occurrence of Class 1 Integrons in Clinical Isolates of Salmonella enterica

Abstract: Screening of non-typhoidal Salmonella enterica clinical isolates (n=20) by PCR revealed the high prevalence of class 1 integrons (45%). Multidrug-resistant (MDR) phenotypes were observed in all integron-positive isolates, regardless of the serotype. A significant correlation was found between the MDR phenotype and the presence of class 1 integrons in the isolates, especially in S. Typhimurium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…14 In this study, class II integron was detected in 21% of the isolates. Previous data confirmed that this class had a lower prevalence.…”
Section: Discussionmentioning
confidence: 52%
“…14 In this study, class II integron was detected in 21% of the isolates. Previous data confirmed that this class had a lower prevalence.…”
Section: Discussionmentioning
confidence: 52%